Control of an Outbreak of Acinetobacter baumannii in Burn Unit in a Tertiary Care Hospital of North India - Shweta Sharma; Nirmaljit Kaur; Shalini Malhotra; Preeti Madan; Charoo Hans (Advances in Public Health)
Acinetobacter infection is increasing in hospitals and now it is considered as a global threat, as it can be easily transmitted and remain viable in the hospital environment for a long time due to its multidrug-resistant status, resistance to desiccation, and tendency to adhere to inanimate surfaces. Outbreaks caused by multidrug-resistant Acinetobacter baumannii (MDRAB) are difficult to control and have substantial morbidity and mortality, especially in vulnerable host. Here we are describing an outbreak of multidrug-resistant Acinetobacter baumannii in burn unit of a tertiary care hospital in India followed by its investigation and infection control measures taken to curtail the outbreak. Outbreak investigation and environmental sampling are the key factors which help in deciding the infection control strategies for control of outbreak. Implementation of contact precautions, hand hygiene, personnel protective equipment, environmental disinfection, isolation of patients, and training of health care workers are effective measures to control the outbreak of MDRAB in burn unit.